Map of Return of Shares and Volume Activity Trading of Companies in Indonesia on The Pandemic Time of Covid-19 - Hersugondo Hersugondo; Abdul Karim; Abdul Rouf (Media Ekonomi dan Manajemen, 2021)
This research was conducted to determine the impact of Covid-19 on the Company’s stock returns and trading volume activity. The covid-19 pandemic event is important for research because it includes investor’s assessment of the information generated in the capital market. This study was conducted to test the following hypotheses: before and after the Covid-19 pandemic was declared a national non-natural disaster, (1) there was a significant average change in the average abnormal return; (2) it is a significant average change in average trading volume activity. This research was conducted using event research methods. The sample for this study comes from 45 companies in the JII index. The analysis tool used is a regression with the SPSS. The descriptive statistic can be confirmed by calculating the standard deviation value. The result shows that the standard deviation range is 0.0002 to 0.03, so the research tool could be described as data obtained is suitable to the measurement variable. The conclusions explain that the events before and after the declaration of the Covid-19 outbreak as a national non-natural disaster have positive and a significant impact on the average abnormal return rate of stock activity and changes in trading volume activity.